An unexpected fluorescent emission of anthracene derivatives in the solid state. (February 2023) - Zhang, Liang; Ding, Liang; Zhou, Shiyuan; Zhang, Feng; Gu, Peiyang
Abstract: Luminescent small molecules in the solid states are of significant importance for organic light-emitting diodes, cell images, fluorescent probes and sensors, owing to the low cost, low toxicity and chemical stability. Herein, two anthracene-based molecules with the same skeleton, but differing in the end group namely M-MMA and M-4VB (methyl methacrylate for M-MMA, 4-vinylbenzeyl for M-4VB) were successfully designed and synthesized. M-4VB exhibits strong green fluorescence with high quantum yield (37%) in the solid state and excellent aggregation-induced emission (AIE) behavior in DMF/water mixtures, while M-MMA shows relatively weak emission. The crystal structures of both M-MMA and M-4VB were successfully obtained in THF/ethanol mixtures. The more rigid environment and stronger intermolecular hydrogen bonding interactions contribute to the enhanced emission behavior of M-4VB at both solid state and aggregation state. The novel and simple synthesis strategy in this work provides a new approach to the transformation from aggregation-caused quenching to AIE molecules with enhanced emission behavior in the solid state. Graphical abstract: Image 1 Highlights: A simple strategy for the transformation from ACQ to AIE molecules containing anthracene moieties was proposed. The two molecules only differed in end group but M-4VB exhibited much better emission behavior. The crystals were for the investigation on intramolecular interactions to explain the different emission behavior.